1998
DOI: 10.1136/jmg.35.12.1009
|View full text |Cite
|
Sign up to set email alerts
|

The C677T mutation of the 5,10-methylenetetrahydrofolate reductase gene is a moderate risk factor for spina bifida in Italy.

Abstract: Objective-To estimate the risk for spina bifida associated with the common mutation C677T of the MTHFR gene in a country with a relatively low prevalence of NTDs.Design-Case-control study. Subjects-Cases: 203 living patients affected with spina bifida (173 myelomeningocele and 30 lipomeningocele); controls: 583 subjects (306 young adults and 277 unselected newborns) from northern and central-southern Italy. Setting-Cases: three spina bifida centres; young adult controls: DNA banks; newborn controls: regional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 5 publications
1
43
1
1
Order By: Relevance
“…Since the A1298C mutation influences enzyme activity and homocysteine and folate concentrations to a lesser extent than does the C677T mutation, it may be expected that the A1298C mutation is a risk factor for NTD, but with a smaller relative risk. On the contrary, we found that the A1298C polymorphism is an important risk factor for the Italian population with a risk associated with the 1298C/C genotype that is even higher than that reported for the homozygous mutant genotype of the C677T mutation (de Franchis et al 1998). MTHFR nucleotide 1298 is located on the regulatory domain of the protein, where it may be involved in protein stabilization (Shan et al 1999).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Since the A1298C mutation influences enzyme activity and homocysteine and folate concentrations to a lesser extent than does the C677T mutation, it may be expected that the A1298C mutation is a risk factor for NTD, but with a smaller relative risk. On the contrary, we found that the A1298C polymorphism is an important risk factor for the Italian population with a risk associated with the 1298C/C genotype that is even higher than that reported for the homozygous mutant genotype of the C677T mutation (de Franchis et al 1998). MTHFR nucleotide 1298 is located on the regulatory domain of the protein, where it may be involved in protein stabilization (Shan et al 1999).…”
Section: Discussioncontrasting
confidence: 46%
“…The C677T mutation was studied in the Italian population, which has a relatively low prevalence of NTDs. In this study, an increased NTD risk was found for the T/T genotype (odds ratio [OR] ϭ 1.73), and the corresponding attributable fraction was 10.8% (de Franchis et al 1998). …”
Section: Abstract Neural Tube Defects ·mentioning
confidence: 86%
“…These proportions were similar between subjects born in the North and in the South. Genotype frequencies were similar in the two sets of controls (newborns and adults) 17 ; therefore, we pooled the sets.…”
Section: Resultsmentioning
confidence: 99%
“…The subjects with spina bifida had been included in another study of MTHFR allelic variants. 17 Of the 203 children with spina bifida, 173 (85%) had myelomeningocele and 30 (15%) had lipomeningocele. All affected children were enrolled from three spina bifida centers in three cities (Genova, Roma, Napoli) with the assistance of the Italian Federation of Spina Bifida and the Hydrocephalus Association.…”
Section: Study Populationmentioning
confidence: 99%
“…Studies from Europe also report that the C677T mutation does not result in a significant risk factor for NTD either independently or in association with other polymorphic alleles involved in folate metabolism. [36][37][38] Moreover, we are the first to present data on MTHFR C677T/A1298C haploid genotypes in combination with RFC-1 A80G variant. Examination of combined genotypes revealed that haplotypes 677CT/1298CC and 677TT/ 1298CC were not observed in our NTD families and controls.…”
Section: Discussionmentioning
confidence: 99%